2022
DOI: 10.1177/08982643211070136
|View full text |Cite
|
Sign up to set email alerts
|

Childbearing Biographies and Midlife Women’s Health

Abstract: Objectives We introduce a “childbearing biography” approach to show how multiple childbearing characteristics cluster in ways significant for midlife health. Methods We analyze the National Longitudinal Survey of Youth 1979 (NLSY79; N = 3992) using mixed-mode Latent Class Analysis with eight childbearing variables (e.g., age at first birth, parity, birth spacing, and mistimed births) to identify how childbearing biographies are associated with midlife health, adjusting for key covariates—including socioeconomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 66 publications
0
4
1
Order By: Relevance
“…Parents also depend on information from their own families, and studies have shown that mothers' understanding of infant development is closely correlated with that of their own mothers [15]. Contrary to our findings [16], a similar Iraqi study found that mothers learned the majority of knowledge about their children's developmental MSs from their own experiences (71.5%), with very small percentages learning it from doctors (16.5%) and PHC institutions (5.5%).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Parents also depend on information from their own families, and studies have shown that mothers' understanding of infant development is closely correlated with that of their own mothers [15]. Contrary to our findings [16], a similar Iraqi study found that mothers learned the majority of knowledge about their children's developmental MSs from their own experiences (71.5%), with very small percentages learning it from doctors (16.5%) and PHC institutions (5.5%).…”
Section: Discussioncontrasting
confidence: 99%
“…The results of the current study indicated a substantial correlation between the mother's work and understanding of the overall development MSs. This went against the findings [16], which showed a strong correlation between homemaker moms' understanding of motor development and their level of education. Regarding parity, the number of delivered kids and the mother's awareness of a child's developmental MSs did not significantly correlate, consistent with a 2015 study that also revealed no significant correlation [17].…”
Section: Discussionmentioning
confidence: 56%
“…An extensive and multidisciplinary body of research investigates the relationship between women's age at first birth and their health later in life (see Hoffman 2015, Mollborn 2017. Many of these studies find evidence that early childbearing increases women's chances of poor health and mortality risk in later adulthood (Angelini and Mierau 2018, Henretta 2007, Mollborn and Morningstar 2009, Thomeer, Reczek and Ross 2022, Williams et al 2015, Williams and Finch 2019. More specifically, Mirowsky (2002Mirowsky ( , 2005-combining data from multiple cohorts of women-found that a first birth prior to age 23 was link to health problems and higher mortality risk.…”
Section: Age At First Birth and Women's Healthmentioning
confidence: 99%
“…Age at first birth has a lasting association with women's health. By midlife, women who began childbearing in their teens and early twenties generally have a higher risk for health problems and mortality risk compared to women who forego or delay motherhood (Henretta 2007, Spence and Eberstein 2009, Thomeer, Reczek and Ross 2022, Williams et al 2015. To explain this finding, social scientists often conceptualize childbearing in adolescence (ages 13-19) and even transitional adulthood (ages 19-22) as a disruptive event for women's socioeconomic attainment (see Hoffman 2015, Mollborn 2017.…”
mentioning
confidence: 99%
“…Surprisingly, most empirical studies assess either time patterns of work-family trajectories as predictors for health outcomes other than physical functioning (cf. Machů et al, 2022), or they look at physical health outcomes but without taking into account the complex ways in which the domains of work and family intertwine throughout the life course (e.g., Thomeer et al, 2022;Wahrendorf et al, 2020). Yet, work-family life courses matter not only for (mental) well-being but also for physical functioning in later life.…”
Section: Introductionmentioning
confidence: 99%